Statistical Accounting as a Digital Measure of the Development of the Region's Adaptation Potential Under Sanctions - N. D. Kremlev (Статистика и экономика)
The purpose of the study is to substantiate the tools for digital measurement of the development of the adaptive potential of the region's population under sanctions using economic and statistical analysis methods. The study uses statistical characteristics that are suitable for creating a model of interaction between internal and external adaptation systems of the region's population. It is assumed that the adaptive potential of a person is determined by the amount of stress they experience over a certain period of time. To characterize the relative values of stress, the theory of population needs is used, in particular: natural-physiological, demographic, social, economic and organizational. The region's adaptive potential includes demographic, labor, social, economic, industrial, organizational, and other types. The materials and methods of the research are the application of official data of the Federal State Statistics Service using economic and statistical analysis methods, structural and dynamic analysis of indicators, as well as methods of theoretical research in the form of generalization, comparison, aggregation and special analytical procedures.According to the results of the review of theoretical approaches, it is concluded that the adaptive potential can be described as a complex object of research. Based on physiological, socio-demographic, activity, economic and other approaches, the author developed and proposed a model for digital measurement of the development of the region's adaptive potential under sanctions. The concept of adaptive potential is clarified as the ability (potency) of population organisms, resources of enterprises and territories, their specific capabilities to produce benefits and change (to adapt) to any situation. A model of interaction between internal and external systems of population adaptation, a method for calculating the aggregate index of development of the region's adaptation potential, and a matrix for estimating the growth rate (weights) of its elements are developed. Analysis of the measurement of the aggregated indices confirmed the assumption about the impact of foreign sanctions on the degree of adaptation of the population of the country's regions. For example, in 2015, the index of adaptive capacity decreased to negative values in all regions of the Ural Federal District and some in the Central Federal District and in subsequent years there was a gradual adaptation of regions to sanctions. The results obtained expand the understanding of the impact of sanctions on the adaptation of the population of regions; they can be used to diagnose socio-economic processes; develop practical recommendations for improving regional policies and strategies for sustainable development in the face of sanctions and other challenges of the time. The considered approach is linked to the tasks set for the Russian system of state statistics in the framework of the program "Digital economy of the Russian Federation".